Evaluation of multiple-flows exhaled nitric oxide in idiopathic and non-idiopathic interstitial lung disease. (27th March 2019) - Cameli, Paolo; Bargagli, Elena; Bergantini, Laura; Refini, Rosa Metella; Pieroni, Maria; Sestini, Piersante; Rottoli, Paola
Abstract: Background: fractional exhaled nitric oxide (FeNO) is a non-invasive and reproducible marker of nitrosative stress and lung inflammation. More recently, FeNO has been proposed as a marker of severity of idiopathic pulmonary fibrosis (IPF) and systemic sclerosis associated ILD. AIM and objectives: to evaluate the role of FeNO in the diagnostic pathway of ILDs. Methods: according to ERS guidelines for exhaled biomarkers in lung diseases, FeNO at multiple flow-rates (50-100-150 and 350 ml s −1 ) and alveolar concentration of NO (CaNO) were collected in 60 healthy controls and 134 patients affected by ILD: 50 with IPF, 19 with fibrotic non-specific interstitial pneumonia, 19 with chronic hypersensitivitis pneumonia (cHP) and 46 with connective tissue disease related ILD (CTD–ILD). ROC curves were performed to investigate the potential role of eNO parameters in discriminating between idiopathic and non-idiopathic ILDs. Results: all ILD groups reported higher levels of FeNO 150–350 ml s −1 and CaNO than controls. Among ILDs, CTD–ILD showed more elevated FeNO 350 ml s −1 and CaNO levels than other ILD. In particular, CaNO reported the best diagnostic accuracy to discriminate CTD–ILD from idiopathic ILDs. Conclusions: patients affected by ILD reported increased FeNO 150–350 ml s −1 and CaNO in respect with healthy controls, indicating a potential role of nitrosative stress in lung fibrosis. The significant difference of CaNO levels between idiopathic ILDs and CTD–ILD is interesting and may suggest that NO is also implicated in lung inflammation associated with rheumatological disease. Further evidence is necessary to establish if CaNO is worthy of attention in the differential diagnosis of ILDs.